Four Different Carotid Atherosclerotic Behaviors Based on Luminal Stenosis and Plaque Characteristics in Symptomatic Patients: An in Vivo Study - Watase, Hiroko (Diagnostics (Basel), 2019)
Correct stratification of ischemic stroke risk allows for the proper treatment of carotid atherosclerotic disease. We seek to differentiate plaque types based on stenosis level and plaque morphology. The Chinese Atherosclerosis Risk Evaluation (CARE–II) study is a cross-sectional, observational, multicenter study to assess carotid atherosclerotic plaques in symptomatic subjects using vessel wall magnetic resonance imaging. Plaque morphology and presence of plaque components were reviewed using multi-contrast magnetic resonance imaging. The carotid arteries were divided into four groups based on stenosis level and plaque components. Out of 1072 ischemic stroke subjects, 452 ipsilateral side carotid arteries were included. Significant stenosis (SS) (≥50% stenosis) with high-risk plaque (HRP) features was present in 37 arteries (8.2%), SS(+)/HRP(−) in 29 arteries (6.4%), SS(−)/HRP(+) in 57 arteries (12.6%), and SS(−)/HRP(−) in 329 arteries (72.8%). The prevalence of SS(−)/HRP(+) arteries in this cohort was substantial and had greater wall thickness than the SS(+)/HRP(−) group. These arteries may be misclassified for carotid revascularization by current guidelines based on the degree of luminal stenosis only. These findings have implications for further studies to assess stroke risk using vessel wall imaging.